Processamento da leitura de palavras por falantes bilíngues: português brasileiro e inglês com e sem TDAH - Silva, Débora Morais Barbosa da (2023)
This dissertation examines bilingual volunteers with and without ADHD. We seek to explore the relationship between bilingualism and ADHD, based on the way bilingual people process word reading. BIALYSTOK et al., (2010), found a long-term effect between these two phenomena, the reduction of vocabulary in two or more languages, but the etiology of each of the phenomena is different. The origin of vocabulary reduction for the bilingual individual is due to the “effort” to manage two or more languages, which may lead to improved executive control, which underlies working memory, task switching, planning and problem solving (KOVÁCS; MEHLER, 2009; SINGH et al., 2015). In contrast to the bilingual subject, individuals with ADHD have its loss of vocabulary because it is associated with weak executive control (BARKLEY, 2020;DIGIROLAMO et al., 2001; ING et al., 2007; SONUGA-BARKE; BITSAKOU; THOMPSON, 2010). We set out to investigate what would happen if the two phenomena were combined? Considering the possibility of an improved executive control for bilinguals and the deficit of ADHD, would it then be beneficial for the subject with ADHD if he were bilingual? Would bilingualism favor the processing of clinical word reading compared to monolingual individuals with ADHD? The hypothesis for our study is that bilingual participants with ADHD would perform equally to bilingual participants without ADHD. Participants were initially separated into two groups according to their linguistic proficiency in the L2 through the VLT (NATION, 1990) with a time limit of 10 minutes as proposed by Souza and Soares-Silva (2015). We carried out a self-monitored reading task of isolated words when the time spent reading the words and the correct answer to the final question were measured. The results indicated that bilingual participants with ADHD performed better on the experimental task, reading the first stimulus and the second word in less time than the group without ADHD. Regarding the rate of correct answers, the control group got more hits than the ADHD group, but even so, participants with ADHD got a significant number of right answers. We found a statistically significant difference for the level of proficiency, the more advanced the shorter the reading time. We found no effect for word frequency. In general, the results of the bilingual subjects with ADHD are in line with our hypothesis, that the groups with and without ADHD would have equivalent responses, but the group with ADHD read the stimuli more quickly than the group without ADHD, presenting evidence that points to enhanced executive control for bilingual subjects.